Integration of traditional and complementary medicine into medical school curricula: a survey among medical students in Makerere University, Uganda - Mwaka, Amos Deogratius; Tusabe, Gersave; Orach Garimoi, Christopher; Vohra, Sunita; Ibingira, Charles (BMJ open, 2019)
To describe the disposition and sociodemographic characteristics of medical students associated with inclusion of traditional and complementary medicine in medical school curricula in Uganda. Design A cross-sectional study conducted during May 2017. A pretested questionnaire was used to collect data. Disposition to include principles of traditional and complementary medicine into medical school curricula was determined as proportion and associated factors determined through multivariate logistic regression.
Keywords: Traditional; Complementary medicine; Medical school curricula; Medical students; Makerere University